A Phenanthrocarbazole‐Based Dopant‐Free Hole‐Transport Polymer with Noncovalent Conformational Locking for Efficient Perovskite Solar Cells. Issue 6 (20th December 2021) - Guo, Yaxiao; He, Lanlan; Guo, Jiaxin; Guo, Yu; Zhang, Fuguo; Wang, Linqin; Yang, Hao; Xiao, Chenhao; Liu, Yi; Chen, Yongsheng; Yao, Zhaoyang; Sun, Licheng
Abstract: Adequate hole mobility is the prerequisite for dopant‐free polymeric hole‐transport materials (HTMs). Constraining the configurational variation of polymer chains to afford a rigid and planar backbone can reduce unfavorable reorganization energy and improve hole mobility. Herein, a noncovalent conformational locking via S–O secondary interaction is exploited in a phenanthrocarbazole (PC ) based polymeric HTM, PC6, to fix the molecular geometry and significantly reduce reorganization energy. Systematic studies on structurally explicit repeats to targeted polymers reveals that the broad and planar backbone of PC remarkably enhances π–π stacking of adjacent polymers, facilitating intermolecular charge transfer greatly. The inserted "Lewis soft" oxygen atoms passivate the trap sites efficiently at the perovskite/HTM interface and further suppress interfacial recombination. Consequently, a PSC employing PC6 as a dopant‐free HTM offers an excellent power conversion efficiency of 22.2 % and significantly improved longevity, rendering it as one of the best PSCs based on dopant‐free HTMs. Abstract : A polymeric hole‐transport material (HTM) based on the phenanthrocarbazole derivative PC6 features a two‐dimensionally conjugated phenanthrocarbazole and S‐O noncovalent conformational locking. Perovskite solar cells employing PC6 as a dopant‐free HTM afforded an excellent power conversion efficiency (PCE) of 22.2 % and long‐term stability.